A Better Way to Measure Operating Performance (or Why the EVA Math Really Matters). Issue 3 (September 2016) - O'Byrne, Stephen F.
Abstract : Most companies rely heavily on earnings to measure operating performance, but earnings growth has at least two important weaknesses as a proxy for investor wealth. Current earnings can come at the expense of future earnings through, for example, short‐sighted cutbacks in investment, including spending on R&D. But growth in EPS can also be achieved by investing more capital with projected rates of return that, although well below the cost of capital, are higher than the after‐tax cost of debt. Stock compensation has been the conventional solution to the first problem because it's a discounted cash flow value that is assumed to discourage actions that sacrifice future earnings. Economic profit—in its most popular manifestation, EVA—has been the conventional solution to the second problem with earnings because it includes a capital charge that penalizes low‐return investment. But neither of these conventional solutions appears to work very well in practice. Stock compensation isn't tied to business unit performance—and often fails to provide the intended incentives for the (many) corporate managers who believe that meeting current consensus earnings is more important than investing to maintain future earnings. EVA doesn't work well when new investments take time to become profitable because the higher capital charge comes before the related income. In this article, the author presents two new operating performance measures that are likely to work better than either earnings or EVA because they reflect the value that can be lost either through corporate underinvestment or overinvestment designed to increase current earnings. Both of these new measures are based on the math that ties EVA to discounted cash flow value, particularly its division of current corporate market values into two components: "current operations value" and "future growth value." The key to the effectiveness of the new measures in explaining changes in company stock prices and market values is a statistical model of changes in future growth value that captures the expected effects of significant increases in current investment in R&D and advertising on future profits and value.